PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN ADOBE FLASH PROFESSIONAL BERBASIS LITERASI UNTUK MENINGKATKAN KREATIVITAS SISWA - Dian Trilaksono; Darmadi Darmadi; Wasilatul Murtafi'ah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This research is a research development that aims to know the validity, practicality, and effectiveness of learning media using Adobe Flash Professional based on literacy to improve student creativity and establish SMK Cendekia Madiun XI Banking as the subject of research with reference to 4D development model until the third stage, that is define , design, and develop. Instruments used in this research include validation sheet for instructional media, questionnaire response to measure the practicality of media, test result of learning result and questionnaire of student creativity to measure media effectiveness. The results of this study are as follows: 1) Learning media developed meet the criteria of validity and the average results obtained from the media validation questionnaire reached 85.42%. 2) Learning media developed meet the criteria of practicality with the average results obtained from the questionnaire of student responses on field trials reached 81.25%. 3) Learning media developed meet the criteria of effectiveness with the average results obtained from the average test results and the average score of student creativity questionnaires on field trials reached 82.95%. Based on the results of this study can be concluded that the learning media using Adobe Flash Professional based literacy to improve student creativity developed by researchers worthy of use in learning.